The effect of food packaging elements on children’s food choices and intake: A systematic review - Arraztio-Cordoba, Alazne; Araque-Padilla, Rafael A.; Montero-Simo, Maria Jose; Olarte-Sanchez, Cristian M. (Frontiers in Nutrition, 2022)
Little can be added about the worldwide concern over the exponential increase in obesity and child overweight problems. Much of the unhealthy eating habits occur at the time of food choice. The enormous influence of marketing strategies in general, and packaging in particular, has been highlighted here. In this respect, public policies that tend to direct choices towards healthier options have been developed. However, the usefulness of such policies will depend on evidence of how different packaging elements can influence children. This systematic review aims to compile the knowledge available to date on the influence of packaging on food choices and eating behaviours in children. Methodologically, the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines have been followed to select papers. We also assessed the risk of bias in the studies analysed using the Newcastle-Ottawa Quality Assessment Scale (NOS). The initial search strategy found 2,627 articles, although only 20 of them met the eligibility criteria. Data from the studies were extracted, categorized, and analysed. The results indicate that most of the packaging elements have some effect on children's food choices or food intake. The use of Cartoon is the element with the most consistent evidence of influence. Despite the number of studies and public initiatives developed to promote this informative and persuasive element, less consistency has been found regarding the effect of Nutrition Labelling. Therefore, the results found should be considered by both governments and organizations when promoting public policies that work for the well-being of children.